Use of Online Public Access Catalogues: A Case study - Bansal, Sonia; Kumar, Sanjeev (Journal of Information and Knowledge, 2017)
IT applications have brought changes in information storage, access and dissemination. OPAC is one of the basic services provided by libraries. The present study throws light on use of OPAC by the students of Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana. A questionnaire based survey on use of OPAC was conducted. The paper discusses various aspects of OPAC use such as frequency of use, ease of use, satisfaction regarding use of OPAC etc.